Pengaruh Media Pembelajaran Berbasis Website (Wordwall) Terhadap Hasil Belajar Peserta Didik Pada Mata Pelajaran Fiqih Kelas VII Di Sekolah Menengah Pertama Muhammadiyah 07 Paciran - Mohammad Fikriansyah Idzi’ Layyinnati (STIT Muhammadiyah Paciran, 2021)
This study uses the application of the classroom action research model (CAR) with the aim of knowing learning outcomes in fiqh class VII subjects through wordwall game media because after using wordwall game media students obtain complete learning outcomes at SMP Muhammadiyah 07 Blimbing, Paciran for the 2020/2021 academic year. . The population in this study were all seventh grade students at SMP Muhammadiyah 07 Blimbing, Paciran for the 2020/2021 academic year, totaling 50 students. In this study, the data collection technique used was the observation method. From the results of data processing questions before using the application of web-based game learning media (Wordwall) and after using the application of web-based game learning media (Wordwall) or commonly referred to as pre-test and post-test, which were tested with the equation formula Product Moment Correlation with significance level of 5% and 95% confidence level and 1% significance level and 99% confidence level, the result of rcount is 0.955. Meanwhile, in the rtable with 50 respondents, it is known that the rtable prices are 0.284 and 0.368. After being compared with rcount, it turns out that rcount is greater than rtable (0.284 < 0.955> 0.478), meaning that Ho is rejected and Ha is accepted. Furthermore, in the interpretation of the assessment, the correlation coefficient found is 0.955, which is between 0.80-1,000, so it is included in the very strong category.